Aligned diphenylalanine nanotube–silver nanoparticle templates for high‐sensitivity surface‐enhanced Raman scattering. (15th September 2017) - Almohammed, Sawsan; Fedele, Stefano; Rodriguez, Brian J.; Rice, James H.
Abstract: Self‐assembly offers potential routes for large‐scale, rapid, and cost‐effective surface‐enhanced Raman scattering (SERS) substrate designs. Here, a highly sensitive SERS template is reported, which utilizes aligned diphenylalanine nanotubes to form a dense packing arrangement of plasmon‐active silver nanoparticles. The template is stable under high laser illumination with a power density of ~6.25 MW/cm 2 in comparison to only silver nanoparticles and enables picomolar and femtomolar probe molecule concentrations to be probed, indicative of single‐molecule SERS detection. Abstract : Aligned FF‐PNTs facilitate a dense packing arrangement of plasmon‐active Ag nanoparticles, creating "hot spots" that enable picomolar and femtomolar probe molecule concentrations to be probed, with demonstrated blinking in surface‐enhanced Raman scattering signal, indicative of single‐molecule detection. The template is stable under high laser illumination with a power density of ~6.25 MW/cm 2 in comparison to only silver nanoparticles.